Carbon dioxide elimination pattern in assessing the risk of an unfavorable outcome in cardiac surgery - O. V. Kamenskaya; I. Yu. Loginova; A. S. Klinkova; D. N. Ponomarev; S. A. Alsov; V. N. Lomivorotov; A. M. Chernyavskiy (Российский кардиологический журнал)
Aim. To assess the influence of resting partial pressure of end-tidal carbon dioxide (PetCO2) levels on the long-term results of cardiac surgery.Materials and methods. This prospective cohort study included 454 patients with coronary artery disease who underwent elective coronary artery bypass graft surgery. Before surgery, all patients underwent pulmonary function tests, including body plethysmography, lung diffusion capacity assessment and cardiopulmonary exercise testing with the determination of ventilatory and gas exchange parameters, including PetCO2 at rest. The endpoint was the 2-year survival rate after surgery.Results. Parameters characterizing the obstructive breathing pattern, the lung diffusion capacity, and resting PetCO2 levels had a significant predictor value in relation to long-term survival after cardiac surgery. Among the baseline clinical and functional characteristics, a significant influence on long-term results was shown by the EuroSCORE II (OR 1,69 (1,26-2,27), p=0,001). The highest sensitivity and specificity in relation to long-term mortality risk after coronary artery bypass grafting was shown by resting PetCO2 value equal to 31 mm Hg (area under the ROC curve 0,74 (0,64-0,86), p<0,001).Conclusion. The resting PetCO2 level below 31 mm Hg in patients with coronary artery disease showed a significant effect on the increased long-term mortality risk after cardiac surgery, which is important for patients with exercise intolerance.